PENGARUH STRUKTUR MODAL DAN CASH FLOW TERHADAP KINERJA KEUANGAN PADA KOPERASI KREDIT SANGOSAY PERIODE 2019-2023 - Rini Andriani; Rinaldi Rinaldi (Journal of Indonesian Comparative of Syari'ah Law, 2025)
Cooperatives play a vital role in driving national economic growth through the application of the principles of mutual cooperation and kinship. One cooperative that has significantly contributed to improving community welfare is the Sangosay Credit Cooperative, which operates in the East Nusa Tenggara region. However, in the 2019–2023 period, this cooperative experienced fluctuations in financial performance due to imbalances in capital structure and cash flow, particularly during the COVID-19 pandemic. This study aims to examine the effect of capital structure and cash flow on the financial performance of the Sangosay Credit Cooperative. The study used a quantitative approach with multiple linear regression analysis based on secondary data from five years of financial statements. The results of the analysis indicate that partially, capital structure and cash flow have a negative and significant effect on financial performance. Meanwhile, simultaneously, both variables have a significant effect with a calculated F value of 7.421, which is greater than the F table of 0.955 and a significance level of 0.050. These findings confirm that effective management of capital structure and cash flow plays a crucial role in maintaining financial stability and improving the operational efficiency of cooperatives.